Strengthening the Character of Global Diversity Based on Integrative Morale in the Teaching Campus Program in Makassar City - Suardi Suardi (Universitas of Muhammadiyah Makassar, 2023)
The main problem is poor students who experience character degradation, so they need character strengthening. The aim of the research is to produce a character strengthening model based on moral integration for elementary school students in Teaching Campus activities in Makassar City. This study used mixed methods research methods. Data collection techniques used questionnaires, observation, interviews and documentation, then analyzed qualitatively and quantitatively. The research results of strengthening the character of global diversity, in the aspect of knowing and appreciating the noble culture of one's own nation and the culture of other nations, have the ability to communicate interculturally in interacting with others, and reflect or be responsible for the practice of diversity which is very good, at all stages of knowing, feeling, moral sinverbal, action, habitus and culture from various teaching campus activities such as teaching assistance by teaching students to be able to interact with all students at school despite different ethnicities, religions and social status and inviting students to think about what good things can be taken from ethnic diversity, religion and social status of students. All of these activities are integrated into intra-curricular activities, co-curricular activities, non-curricular and extra-curricular activities involving school principals, teachers (classes, subjects, counseling), students, lecturers and parents. Strengthening the character of the Pancasila Student Profile in Teaching Campus activities is carried out on an integrative basis of morals and social collaboration.